Impact on Participation and Autonomy Questionnaire (IPA): Reliability and Validity of the Chinese Version for Stroke Survivors - He YN; Qin XH; Lv JH; Guo YP (International Journal of General Medicine)
Ya-Nan He,* Xiao-Huan Qin,* Jian-Hong Lv, Yan-Ping Guo Department of Nursing, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Hong Lv; Yan-ping Guo, Department of Nursing, Shanghai East Hospital, School of Medicine, Tongji University, No. 150 Jimo Road, Pudong New Area, Shanghai, 200120, People’s Republic of China, Tel +86-18930805118 ; +86-13764211995, Email lv2253jh6@outlook.com; gyp13764211995@126.comPurpose: This study aimed to evaluate reliability and validity of the Chinese version of the Impact on Participation and Autonomy Questionnaire (IPA-C) for people with stroke.Methods: The English version of the IPA (IPA-E) was translated into the Chinese version using the protocol for linguistic validation of patient-reported outcome instruments. In total, 421 patients diagnosed with first-ever stroke participated in this study. A cross-sectional study with a test–retest subsample was conducted. Three reliability evaluation methods were used to assess the reliability of IPA-C. Internal consistency reliability was evaluated by calculating the Cronbach’s alpha and split-half reliability. Split-half reliability was recorded using the Guttman split-half coefficient. Item reliability was assessed using test–retest reliability. Validity content and construct validity were used to assess the IPA-C validity.Results: IPA-E consists of five domains: autonomy indoors, family role, autonomy outdoors, social life and relationships, and work and education opportunities. In this study, the domain ‘work and educational opportunities’ and the item ‘My chances of having an intimate relationship are’ were excluded from the analysis. Because they were not applicable to most participants. So, the first part (IPA-C-I), contained 25 items across 4 subscales (Autonomy Indoors, Family Role, Autonomy Outdoors, Social Life and Relationships). The second part (IPA-C-II), the experience of problems, contains further 7 questions, which are 7 domains (mobility, self-care, activities, economic management, leisure, social life and relationships, and helping others). The Cronbach’s alphas of the IPA-C-I was 0.962, IPA-C-II was 0.823, and 0.968 (autonomy indoors), 0.966 (Family role), 0.870 (Autonomy outdoors), 0.913 (Social life and relationships). The Guttman Split-Half Coefficient of the IPA-C-I was 0.792. Item reliabilities estimated from the test-retest ranged from 0.915 to 0.975. The overall content validity index was 0.949. Four factors emerged from the 25 items, accounting for 82.918% of the variance with item loadings above 0.40.Conclusion: The IPA-C can be considered a valid and reliable instrument for assessing participation and autonomy in patients with stroke. Later, researchers could choose IPA-C as a good tool to evaluate perceived participation and problems in stroke patients. However, in patients with a variety of diagnoses and other cultural backgrounds, further assessment of psychometric properties is needed.Keywords: Participation, WHO-ICF, autonomy, stroke, rehabilitation, outcome assessment, IPA